? ?Antibacterial and Phytochemical Studies on Dicoma tomentosa: Short Communication (Biological Sciences - PJSIR, 1995)
The results represented in Table 1 indicate that a mildbroad spectrum antibacterial activity was found in theextracts of flowers and roots of Dicoma tomentosa. Bothflowers and roots at 1000 ug/ml cone. have completelyinhibited all the tested strains of Shigella but have notshown activity against any Salmonella species.